Sustainable museum culture in the post-pandemic city: Case study of Skopje - Velinova Ana; Batakoja Meri; Pavlov Zoran (University American College Skopje, 2021)
The pandemic of COVID-19 affected social life and life in general in many ways. Human habits and living in the city that seemed to work for decades are being questioned in order to uncover a novel approach to using resources in times of social restrictions. City functions like transportation, workplace and services were quickly adapted to new circumstances, while others like culture and leisure remained entirely frozen. The aim of the paper is to review culture and the potentials in time of social restrictions through the case study of the city of Skopje. The focus of the paper is museum culture, a field that is also stagnant for decades and has the traditional museum building as its main representation. The need for a more sustainable museum model beyond the museum building is now more evident than ever. While European museological discourses in the last half-century widely accepted the models of open-air museums, the state of interpreting open-air heritage through a museological paradigm is generally absent on the territory of the city of Skopje. Open-air museums aim at open-air interpretation of heritage, while understanding heritage not as a protected status-quo, but as a resource that has an intrinsic role in society at present. The advantage of open-air museums is in the active use of heritage resources, in promoting living heritage and culture, mediating authentic experience and the immediate relation to visitors. The paper will investigate the potentials of heritage resources on the territory of Skopje. The case study on sustainable museum culture in Skopje will focus on mapping heritage resources, review of the state of protection and readability of heritage, accessibility and capacity of heritage for open-air museum use, the potentials for applying the concept of open-air museology through programmatic and spatial interventions, etc.
Keywords: 330; open-air museum; Skopje; new museology; sustainable; museum culture; heritage